2018
DOI: 10.3389/fcimb.2018.00150
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus on Sinus Culture Is Associated With Recurrence of Chronic Rhinosinusitis After Endoscopic Sinus Surgery

Abstract: Objectives: Identify whether identification of S. aureus on conventional culture is a predictor of success or failure after ESS followed by budesonide nasal irrigations (BUD) in chronic rhinosinusitis (CRS) patients at high risk of recurrence.Methodology: Prospective clinical trial including 116 patients from a tertiary care center at high-risk of disease recurrence following ESS+BUD. Blood samples, microbial swabs, and SNSS/SNOT-22 were taken on the day of surgery (Visit-1) and 4 months postoperatively (Visit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 25 publications
(29 reference statements)
6
16
0
Order By: Relevance
“…Using our group's criteria for high-risk patients, 5 we demonstrated through a prospective clinical trial that presence of pre-and post-ESS Staphylococcus aureus was a negative microbiologic biomarker for disease recurrence in patients having undergone ESS followed by saline irrigations with budesonide respules (BNI). 6 We further demonstrated S aureus's deleterious effect on epithelial repair, 7 which was in concordance with the clinical findings of the prospective trial.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…Using our group's criteria for high-risk patients, 5 we demonstrated through a prospective clinical trial that presence of pre-and post-ESS Staphylococcus aureus was a negative microbiologic biomarker for disease recurrence in patients having undergone ESS followed by saline irrigations with budesonide respules (BNI). 6 We further demonstrated S aureus's deleterious effect on epithelial repair, 7 which was in concordance with the clinical findings of the prospective trial.…”
supporting
confidence: 84%
“…The mechanism behind S aureus ’s CRS pathogenesis and tendency for poor prognosis has been described through various hypotheses, whether it be its biofilm‐forming capacities, 34 its intraepithelial presence, 35 its potential for immunity reduction, 36 or its impairment of epithelial repair, 7 among others. What remains evident is that S aureus is a strong marker for CRS outcome, both pre‐ and post‐ESS. 6 The benefit of adding AZI, and its capacity to influence S aureus clearance, is demonstrated clinically in this study, whereas our group also previously showed that the mechanism behind this effect may be associated with the CRS epithelium healing properties AZI has through its rho‐kinase inhibitor‐like properties, even in the presence of S aureus .…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…aureus has often been reported and associated with refractory CRS. [47][48][49] It is interesting to see that azithromycin may play a role in decreasing this pathogen in such a difficult-to-treat population. Its underlying anti-staphylococcal mechanism of action remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus has often been reported and associated with refractory CRS 47‐49 . It is interesting to see that azithromycin may play a role in decreasing this pathogen in such a difficult‐to‐treat population.…”
Section: Discussionmentioning
confidence: 99%